Unveiling the Relationship Between Sustainability Certification and Zero Deforestation on Financial Performance in Crude Palm Oil Plantation - Sinaga, Ruth Tesalonika; Nainggolan, Yunieta (Journal Integration of Management Studies, 2025)
The purpose of this research study is to investigate the relationship between key financial performance indicators and financial leverage in decision-making for achieving sustainable performance, as measured by sustainability certification and zero deforestation, in the palm oil industries of Indonesia and Malaysia from 2021 to 2023. This study employs panel data regression and logistic regression, using data from 25 palm oil plantations in Indonesia and Malaysia from 2021 to 2023. The data analysis was conducted using STATA software to process and interpret the multiple regression models. This research employs a dual-lens empirical framework, focusing on sustainable certification and zero deforestation. The results reveal that financial performance has a negative, yet insignificant, relationship with sustainable certification and zero deforestation. Confirming that sustainable practices do not heavily rely on financial structure. Nonetheless, financial leverage has a negative insignificant relationship with sustainable certification or zero deforestation. This suggests that a higher debt ratio is associated with a lower likelihood of adopting sustainable practices. Otherwise, other independent variables, such as liquidity, firm size, and ESG score in zero deforestation, have a positive and significant association, suggesting that larger firms with capital flexibility and a high ESG score are more likely to comply with the zero deforestation policy. For sustainable certification, only the ESG score shows a positive and significant association with sustainable certification. This suggests that palm oil plantations with consistently high ESG scores are more likely to obtain sustainable certification. This research provides broad insight for organizations related to sustainability and managerial insights to support the transparency and credibility of reporting sustainable performance of palm oil plantations in Indonesia and Malaysia.